2017
DOI: 10.1007/s12603-016-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cardiac rehabilitation for prevention and treatment of sarcopenia in patients with cardiovascular disease - a retrospective cross-sectional analysis

Abstract: The present findings suggest that CCR is a promising strategy for prevention and treatment of sarcopenia in patients with CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…Furthermore, the ratio of peak VO 2 /BW and the SMI signicantly higher in patients with statin treatment than in those without statin treatment. 21) Statin inhibits enhanced neutrophil function after reperfusion. As a result, statin treatment can improve liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ratio of peak VO 2 /BW and the SMI signicantly higher in patients with statin treatment than in those without statin treatment. 21) Statin inhibits enhanced neutrophil function after reperfusion. As a result, statin treatment can improve liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of sarcopenia was performed by the diagnosis algorithm recommended by the guidelines of the Asian Working Group for Sarcopenia, as described previously. [13][14][15] Briefly, sarcopenia was diagnosed based on measurements of muscle mass, muscle strength, and physical performance. In practice, sarcopenia was diagnosed on the basis of low skeletal mass index (SMI; <7.0 kg/m 2 in male patients and <5.7 kg/m 2 in female patients) associated with either low handgrip strength (<26 kgf in male patients and <18 kgf in female patients) or low gait speed (<0.8 m/s).…”
Section: Diagnosis Of Sarcopeniamentioning
confidence: 99%
“…Skeletal muscle as a live tissue has a crucial role in metabolic health, strength and athletic performance and more importantly, skeletal tissue is capable of remarkable plasticity [ 31]. Skeletal muscle mass (SMM) plasticity is a result of the adaptation process that leads to increase or decrease of SMM [31][32][33]. Sarcopenia is a well-known term utilized to define the phenomenon of loss of SMM and strength that occurs with aging [ 32,33].…”
Section: Importance Of Skeletal Muscle Massmentioning
confidence: 99%
“…Skeletal muscle mass (SMM) plasticity is a result of the adaptation process that leads to increase or decrease of SMM [31][32][33]. Sarcopenia is a well-known term utilized to define the phenomenon of loss of SMM and strength that occurs with aging [ 32,33]. On the other side, many studies have shown the influence of the training on fat-free mass (FFM) and SMM [34][35][36].…”
Section: Importance Of Skeletal Muscle Massmentioning
confidence: 99%